2017
DOI: 10.3390/ijms18112388
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes of Copaiba (Copaifera multijuga Hayne) Oleoresin and Cyclodextrins: Physicochemical Characterization and Anti-Inflammatory Activity

Abstract: Complexation with cyclodextrins (CDs) is a technique that has been extensively used to increase the aqueous solubility of oils and improve their stability. In addition, this technique has been used to convert oils into solid materials. This work aims to develop inclusion complexes of Copaifera multijuga oleoresin (CMO), which presents anti-inflammatory activity, with β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD) by kneading (KND) and slurry (SL) methods. Physicochemical characterization was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
6
21
0
2
Order By: Relevance
“…Figure 2 depicts the FT-IR spectra of EOO, β-CD, HP-β-CD and the EOO-β-CD and EOO-HP-β-CD inclusion complexes obtained by either kneading (KND) or slurry (SL). The EOO spectrum ( Figure 2A) showed relevant bands at wavenumbers of 2924-2849, 1745, 1458 and 1161 cm −1 that can be assigned to C-H stretching vibrations, C=O stretching vibrations, C=C asymmetric deformation and C-O stretching vibrations, respectively, while the β-CD spectrum ( Figure 2B) showed others at 3302, 1155 and 1024 cm −1 , corresponding to O-H stretching vibrations, C-O asymmetric deformation and C-O-C symmetric stretching vibrations, thereby confirming the results of Pinheiro et al [2]. As expected, the HP-β-CD spectrum (Figure 2E) exhibited the same characteristic bands detected for β-CD, besides the additional band at 2918 cm −1 corresponding to C-H stretching vibrations, confirming the observations by Medarević et al [35].…”
Section: Determination Of the Interaction Energysupporting
confidence: 88%
See 3 more Smart Citations
“…Figure 2 depicts the FT-IR spectra of EOO, β-CD, HP-β-CD and the EOO-β-CD and EOO-HP-β-CD inclusion complexes obtained by either kneading (KND) or slurry (SL). The EOO spectrum ( Figure 2A) showed relevant bands at wavenumbers of 2924-2849, 1745, 1458 and 1161 cm −1 that can be assigned to C-H stretching vibrations, C=O stretching vibrations, C=C asymmetric deformation and C-O stretching vibrations, respectively, while the β-CD spectrum ( Figure 2B) showed others at 3302, 1155 and 1024 cm −1 , corresponding to O-H stretching vibrations, C-O asymmetric deformation and C-O-C symmetric stretching vibrations, thereby confirming the results of Pinheiro et al [2]. As expected, the HP-β-CD spectrum (Figure 2E) exhibited the same characteristic bands detected for β-CD, besides the additional band at 2918 cm −1 corresponding to C-H stretching vibrations, confirming the observations by Medarević et al [35].…”
Section: Determination Of the Interaction Energysupporting
confidence: 88%
“…Similarly to what observed by Pinheiro et al [2], HP-β-CD showed an endothermic peak ( Figure 6B) with Tonset = 37.25 °C (ΔH = 6.47 J/g and Tpeak = 37.05 °C) related to water release from its β-CD exhibited an endothermic peak ( Figure 6A) involving ∆H = 231.02 J/g with Tonset = 30.94 • C and Tpeak = 73.71 • C, likely due to water release from its cavity, and a second event occurred at Tonset = 223.50 • C (∆H = 0.75 J/g and Tpeak = 226.68 • C), similarly to the observations of Nascimento et al [3]. It was not possible to identify eventual endothermic events related to β-CD mass loss at high temperatures [2,40] because a maximum temperature of 300 • C was set in this study. β-CD complexes obtained by KND and SL showed similar behavior ( Figure 6A) with Tonset = 27.07 • C (∆H = 48.46 J/g and Tpeak = 42.72 • C) and 24.07 • C (∆H = 142.10 J/g and Tpeak = 48.86 • C), respectively, both related to dehydration, but occurring at lower temperatures when compared to β-CD.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 85%
See 2 more Smart Citations
“…However, sample PVA-O presented also bands related to copaiba oil. The copaiba oil bands were observed at: 2922 cm -1 , ν(-CH); 2854 cm -1 , ν(-CH 2 ); 1743 cm -1 , ν(-C=O); 1415 cm -1 , δ(-CH) [35] .…”
Section: Microstructural Analysismentioning
confidence: 99%